2018
DOI: 10.1073/pnas.1710215115
|View full text |Cite
|
Sign up to set email alerts
|

Hamilton's inclusive fitness maintains heritable altruism polymorphism through rb = c

Abstract: How can altruism evolve or be maintained in a selfish world? Hamilton's rule shows that the former process will occur when > -the benefits to the recipients of an altruistic act, weighted by the relatedness between the social partners , exceed the costs to the altruists-drives altruistic genotypes spreading against nonaltruistic ones. From this rule, we infer that altruistic genotypes will persist in a population by forming a stable heritable polymorphism with nonaltruistic genotypes if = makes inclusive fitne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 49 publications
(64 reference statements)
0
32
0
Order By: Relevance
“…Consistent with the equation's predictions, phylogenetically controlled comparative analyses implicate monogamy, or at least reduced promiscuity, as the most probable ancestral states across social Hymenoptera, cooperatively breeding birds, and social mammals [3,4,8]. Also, some studies that attempted to measure the inclusive fitness of helpers found that Hamilton's condition for advantageous helping is met [13,14]. Indeed, the apparent necessity that the evolution of both facultative and obligate sterility must pass through a ‘monogamy window' was presented as a clear refutation of NTW [15].…”
mentioning
confidence: 87%
“…Consistent with the equation's predictions, phylogenetically controlled comparative analyses implicate monogamy, or at least reduced promiscuity, as the most probable ancestral states across social Hymenoptera, cooperatively breeding birds, and social mammals [3,4,8]. Also, some studies that attempted to measure the inclusive fitness of helpers found that Hamilton's condition for advantageous helping is met [13,14]. Indeed, the apparent necessity that the evolution of both facultative and obligate sterility must pass through a ‘monogamy window' was presented as a clear refutation of NTW [15].…”
mentioning
confidence: 87%
“…This addresses the general theoretical question of whether moral character and values are distinct from the temperament and action tendencies which personality inventories typically tap (Cawley III, Martin, & Johnson, 2000). Also important to analyse is whether any such distinct, heritable strategies for principled versus opportunistic justice sensitivity share common genetic substrates with other psychological traits that serve to sustain cooperation for the greater common good-such as altruism (Rushton et al, 1986;Wang & Lu, 2018) and trust (e.g., Cesarini et al, 2008)-versus serve to maximize adaptive fitness gains over others, such as social dominance and the monopolization of territory and resources (Kleppestø et al, 2019). This possibility can be tested with our genetically informative sample.…”
Section: Exploring Justice Concerns With Gentically Informative Datamentioning
confidence: 99%
“…A study that does look at polymorphisms is Wang and Lu (2018) . In this study, players have one of two different roles; there are breeding pairs, which are the potential recipients of help, and potential helpers.…”
Section: Implications For Empirical Tests Of Hamilton’s Rulementioning
confidence: 99%